Cu(II), Zn(II), and Cd(II) Complexes of L-Asparagine: Preparation, Characterization and Electrochemical Properties - Halim, Abdul; Rahman, Md Shahidur; Bakshi, Pradip K; Shaikh, A A (Dhaka University Journal of Science, 2025)
L-asparaginato complexes of Copper(II), Zinc(II) and Cadmium(II) were synthesized from their respective metal oxide and L-asparagine. These prepared complexes were characterized by their metal content analysis, infrared, and ultravioletvisible spectral studies, magnetic susceptibility measurement, thermal analysis, and cyclic voltammetric measurement. Physico-chemical investigations reveal that [M(OOCCHNH2CH2CONH2)2], (M = Cu(II), Zn(II), and Cd(II)) is the general formula for the complexes. L-asparagine combines with metal oxides to form bis(L-asparaginato)metal(II) complexes in which the metal(II) ion is hexa-coordinated by the O- anion of the carboxylate ion, the N atom of the amino group, and the O atom of the side chain carboxamide group from each of the two asparaginato species. The statement is corroborated by the analyses conducted for these complexes. The redox behaviours of the metal ion, both in its free state and when complexed, exhibit notable differences, as demonstrated by voltammetric investigations. Both peak currents and peak potentials respond sensitively to the complexation process, as it is expected. Dhaka Univ. J. Sci. 73(1): 31-37, 2025 (January)